Comportamiento de dos cultivares de zanahoria Daucus carota L. frente a patógenos - Méndez Lavayen, Kilma Ximena (2017)
The following work was carried out in the "Carrizal" Mariscal Sucre parish of Milagro, province of Guayas, in the dry season of 2016. It has the following geographical coordinates S 20 02'28¨ W 79 0 33'45¨. . The objectives were: a) To evaluate the agronomic behavior of the treatments studied. B) Determine the best fertilization dose for the cowpea crop INIAP 463. c) Carry out the economic analysis of the treatments studied. As genetic material that was used in the project seeds of fréjol variety INIAP - 463. Application of Nitrogen, Micro Potassium and Macro elements to the soil. For the evaluation of the present work, the completely randomized block design (DBCA) with trifactorial arrangement 2 x 2 x 2 and with three repetitions was used. For the comparison of means the Duncan's multiple range test was used with 5% probability It was concluded: a) In the evaluation of the agronomic behavior we have that in the treatment eight (N160 K O 60 Con) presented the best averages in the physiological variables evaluated plant height, stem diameter, pod length, number of grains By pods, number of pods, weight of one hundred seeds and yield being established that with this combination we obtain plants of greater vigor. B) As the best fertilization dose we have that the combination of Nitrogen 160 kg / ha Potassium 60 kg / ha with application of micronutrients helps us to obtain better yields determining that this is the best dose of application. C) In the economic analysis it was determined that treatment four (N160 K2 O 60 Con) proved to be the most profitable with a TRM of 281.96% because it has a low variable cost value.